Pushing the boundaries of visibility - Kirstin Natalija Stojadinovic 1995- (2021)
Pornographic media in Iceland has so far rarely been discussed from a visual point of view. In the decades of the mid 20th century, explicit imagery became more and more visible in mainstream media along with the wave of sexual liberation taking post-war Europe by storm. To this day, pornography is banned under Icelandic law and has been causing a tug of war between what can and can’t be showcased when it comes to sex. I investigate the often cloudy line between the obscene and the appropriate and how it translates visually by examining examples of this conflict. The “sjoppurit”, magazines typically sold at kiosks are particularly interesting as they provide an abundance of visual material of the time period that became defining for pushing the boundaries of visibility. By using theoretical texts from sociologist Pierre Bourdieu and film scholar Linda Williams I approach the concept pornography from different angles, analysing space, accessibility and class and applying them to the Icelandic cultural scene.